Physical development and functional status of women 20-35 years old, involved in swimming - Liliia Sheiko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: determining changes in physical development and functional state of women 20-35 years old, engaged in swimming. Material & Methods: 20 women aged 20-35 years old took part in the study, which consisted of two groups: the main group (MG) and the control group (CG). The OG included women swimming in the fitness and fitness groups of the author's swimming school of Yu. V. Bliznyuk and Pioneer pool (water sports school named after Yana Klochkova); in the CG - women who lead active lifestyles, but in health groups are not engaged, swimming only on weekends. The tested people had the same swimming preparedness. Applied: survey, testing, instrumental methods for studying the cardiovascular system. Lung capacity and dynamometry were determined. To study the functional reserves of the respiratory and cardiovascular systems, the Skibinsky index was used. The obtained quantitative data were processed by the methods of mathematical statistics. Results: the study suggests that in women of 20-35 years old swimming lessons cause changes in physical development and functional state. According to the parameters of the physical development of women of MG and CG swimming during the year has a positive effect on the body. First of all, swimming helps to improve the state of the cardio-respiratory system and the strength abilities of women. Conclusions: the positive effect of swimming on the physical development and functional status of women aged 20-35 years engaged in recreational swimming is substantiated and proved.